Land-Use Modelling in Planning Practice - Koomen, Eric (Springer Nature, 2011)
This book provides an overview of recent developments and applications of the Land Use Scanner model. Internationally recognized as among the best of its kind, this versatile model can be applied at a national level for trend extrapolation, scenario studies and optimization, yet can also be employed in a smaller-scale regional context. Alongside these practical examples from the Netherlands, readers will find discussion of more theoretical aspects of land-use models as well as an assessment of various studies that aim to develop the Land-Use Scanner model further. Spanning the divide between the abstractions of land-use modelling and the imperatives of policy making, this is a cutting-edge account of the way in which the Land-Use Scanner approach is able to interrogate a spectrum of issues that range from climate change to transportation efficiency. Aimed at planners, researchers and policy makers who need to stay abreast of the latest advances in land-use modelling techniques in the context of planning practice, the book guides the reader through the applications supported by current instrumentation. It affords the opportunity for a wide readership to benefit from the extensive and acknowledged expertise of Dutch planners, who have originated a host of much-used models.